Use of Endemic Date Palm (Phoenix dactylifera L.) Seeds as an Insoluble Dietary Fiber: Effect on Turkey Meat Quality - Mohamed Ali Bouaziz; Brahim Bchir; Tayssir Ben Salah; Abir Mokni; Hajer Ben Hlima; Slim Smaoui; Hamadi Attia; Souhail Besbes (Journal of Food Quality)
In order to enhance the quality of a meat product, turkey burgers with a low-fat and a high-fiber level were formulated by the incorporation of insoluble fibers from Tunisian Deglet Nour date seeds as insoluble fiber concentrate (IFC) at 3%, 5%, and 10% (w/w). Compared to Deglet Nour date seeds powder (DSP), physicochemical results revealed that IFC presented higher (P < 0.05) levels in carbohydrates at 88.85% and lower values of fat (5.94%), protein (3.81%), and ash (2.35%). For the technofunctional properties, IFC improved the oil-holding capacity (OHC) by 57.14% compared to DSP. IFC addition into turkey burgers was also instrumentally investigated by color (L∗, a∗, and b∗) and textural parameters (hardness, cohesiveness, adhesiveness, and elasticity) and sensory attributes using a 5-point hedonic scale. Furthermore, IFC changed significantly the color of the formulated products. In addition, hardness and adhesiveness values of all experiments increased significantly (P < 0.05) with the increase of the incorporation levels compared to the control sample. Regarding sensory analysis, formulated with 5 % IFC, turkey burger samples were most appreciated by the panel with higher (P < 0.05) overall acceptability. Additionally, two multivariate exploratory techniques, namely, Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA), were used to all obtained data describing the main characteristics attributed to refrigerated turkey meat samples. The applied chemometric approaches were useful in discriminating meat samples and therefore offer an approach to rely interrelationships between meat quality traits. Overall, the findings demonstrate the potential functional and economic utility of IFC as a promising ingredient for future healthy meat applications.